(untitled) (ModaPalavra e-periódico, 2009)
Just a few thinkers had dedicated themselves to think about the Fashion phenomenon. The presented piece aims to exemplify the possibility of philosophic exercise also on these fields, testifying its relevance. Starting by bringing those already registered claims, made by those recognized thinkers, for deeply reflection about such peculiar phenomenon, the exercise itself will be over the piece “L’empire de l’éphémère”, by Gilles Lipovetsky, looking for demonstrate how a deeper philosophical reflection may enlarge what is already announced. By the end, will be presented some questions regarding Brazilian’s fashion academical world, which answers seems not enough argued.